Pendidikan Karakter Menurut KH. Hasyim Asy’ari Dan Relevansinya Di Era Industri 4.0. - muhammad azam khairuman; Waslah -; Khoirur Roziqin (JoEMS (Journal of Education and Management Studies), 2020)
Hasyim Asy'ari is a figure of a great scholar who has gained recognition of integrity, quality and morality in responding to various problems experienced by the community, quite intense in making positive contributions. Both in the form of movement, struggle and thought activities. This study aims to determine 1) character education according to KH. Hasyim Ash'ari, 2) its relevance in the Industrial Revolution Era 4.0. Therefore in this thesis research, the writer uses qualitative methods with the type of Library Research research. And in order to get a complete and overall picture of the problem discussed, the authors use inductive analysis, deductive analysis and descriptive. The results of this thesis research, that character education according to KH. Hasyim Asy'ari covers the character of the student towards himself, the character of the student towards the educator, the character of the student towards the subject, the character of the educator towards himself, the character of the educator in teaching and learning, the character of the educator towards the student and the characters related to the textbook. While the relevance of character education according to KH. Hasyim Ash'ari in the era of the industrial revolution 4.0 is still relevant and not out of date. Character education according to KH. Hasyim Asy'ari emphasizes the aim of Islamic education itself, which is to make a whole person who has a balance between strong faith, high scientific competence, strong mentality and good social life in the family, school, and community environment. in general. Although character education according to KH. Hasyim Ash'ari is classified as a classic but still very relevant to be applied in the era of the industrial revolution 4.0 that is happening now.